Upaya Meningkatkan Hasil Belajar Biologi Siswa melalui Model Pembelajaran Discovery Learning di Kelas XI. IPA.I SMAN 2 Lengayang - Idawati Idawati (Departement of Mathematics Education, 2023)
This study aims to disclose information and discuss Efforts to Improve Students' Biology Learning Outcomes Through the Discovery Learning Learning Model in Class XI. IPA.1 SMAN 2 Lengayang. This type of research is classroom action research (CAR). This research was conducted at SMAN 2 Lengayang, Pesisir Selatan District. The subjects of this research were students of class XI. IPA.1 SMAN 2 Lengayang, totaling 32 people. This research will be carried out in the odd semester of the 2022/2023 school year. The research procedure consisted of two cycles with two meetings in each cycle. Each cycle consists of four stages of research namely planning, implementation, observation and reflection. Data collection in this study was carried out using field note techniques, observations, written tests, and documentation. Data analysis techniques use percentage formulas and data reduction. The results of this study indicate that the Discovery Learning Learning Model improves Biology learning outcomes for Class XI students. IPA.1 SMAN 2 Lengayang with the act of giving awards, this can be seen from the average value of the research results of students who completed the first cycle, namely 59% or 19 people out of 32 students with an average value of 80.47. In Cycle II, 88% or 28 students out of 32 students completed the pass with an average score of 81.56. From the research results of Cycle I and Cycle II, it can be concluded that the Discovery Learning Learning Model can Improve Student Biology Learning Outcomes in class XI.IPA.I SMAN 2 Lengayang.